Impact of gadolinium on the structure and magnetic properties of nanocrystalline powders of iron oxides produced by the extraction-pyrolytic method - Serga, Vera E.; Burve, Regina; Maiorov, Mikhail M.; Krūmiņa, Aija P.; Skaudžius, Ramūnas; Žarkov, Aleksej; Kareiva, Aivaras A.; Popov, Anatoli I. (MDPI AG, 2020)
Interest in magnetic nanoparticles is primarily due to their practical use. In this work, for the production of nanocrystalline powders of pure and gadolinium doped iron oxides, the extraction-pyrolytic method (EPM) was used. As a precursor, either iron-containing extract (iron (III) caproate in caproic acid) or its mixture with gadolinium-containing extract (gadolinium (III) valerate in valeric acid) was used. The mixed precursor contained 0.5 mol %, 2.5 mol %, 12.5 mol %, 50 mol %, and 75 mol % gadolinium in relation to the iron content. The formation of iron oxide phases, depending on the preparation conditions, was investigated. According to the results obtained, it was demonstrated that the presence of more than 2.5 mol % gadolinium additive in the mixed precursor inhibits the magnetite-to-hematite transformation process during thermal treatment. Produced samples were characterized by XRD and SEM methods, and the magnetic properties were studied.
The work has been done in frame of the TransFerr project. It has received funding from the European Union’s Horizon 2020 research and innovation program under the Marie Sklodowska-Curie grant agreement No. 778070. This research was also supported by Latvian Research Council project lzp-2018/1-0214. A.I.P. appreciates support from the Estonian Research Council grant (PUT PRG619).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Coercivity; Extraction-pyrolitic method; Gadolinium impact; Iron oxides; Magnetization; Nanostructures